APPLICATION OF THE MULTICRITERIA DECISION-MAKING METHOD TO SELECT THE MOST OPTIMAL BLASTING GEOMETRY: PT INDOCEMENT TUNGGAL PRAKARSA, CITEUREUP, BOGOR REGENCY, INDONESIA - Shukura Muji, Auaradha
Blasting is one of the critical activities in mining activity. Improper blasting geometry can lead to undesirable results, such as poor fragmentation, fly rock, the value of ground vibration, and air blast that exceeds the quality standard. The selection of the optimal blasting geometry needs to consider various aspects, such as technical, environmental, security, and economic aspects. Consideration of various aspects in determining the optimal blasting geometry using conventional methods yields inaccurate results. Method use Multi-Criteria Decision Making (MCDM) makes it possible to determine the blasting geometry by considering various aspects. Three MCDM methods were used in this paper, Analytic Hierarchy Process (AHP), Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), and Weighted Aggregated Sum Product Assessment (WASPAS). The aspects considered are technical (fragmentation), economical (use of explosives), and security (fly rock, ground vibration, and air blast). AHP pairwise comparison uses determining the weight of the fragmentation parameter, powder factor, fly rock, ground vibration, and air blast. The TOPSIS and WASPAS methods were used in the second step to rank the various alternative blasting geometries and determine the most optimal blasting geometry. In the third step, a sensitivity analysis will be performed to see what changes occur when the relative importance can be changed. The results of this study obtained the fourth blasting geometry with a hole diameter of 4 inches, a burden of 3.5 m, spacing of 5 m, stemming of 3,14 m, subdrill of 1 m, and 9 m hole depth as the best blasting geometry for blasting operations at PT Indocement Tunggal Prakarsa.